Integrated approach to prevent functional decline in hospitalized elderly: the Prevention and Reactivation Care Program (PReCaP) - de Vos Annemarie JBM; Asmus-Szepesi Kirsten JE; Bakker Ton JEM; de Vreede Paul L; van Wijngaarden Jeroen DH; Steyerberg Ewout W; Mackenbach Johan P; Nieboer Anna P (BMC Geriatrics, 2012)
Abstract Background Hospital related functional decline in older patients is an underestimated problem. Thirty-five procent of 70-year old patients experience functional decline during hospital admission in comparison with pre-illness baseline. This percentage increases considerably with age. Methods/design To address this issue, the Vlietland Ziekenhuis in The Netherlands has implemented an innovative program (PReCaP), aimed at reducing hospital related functional decline among elderly patients by offering interventions that are multidisciplinary, integrated and goal-oriented at the physical, social, and psychological domains of functional decline. Discussion This paper presents a detailed description of the intervention, which incorporates five distinctive elements: (1) Early identification of elderly patients with a high risk of functional decline, and if necessary followed by the start of the reactivation treatment within 48 h after hospital admission; (2) Intensive follow-up treatment for a selected patient group at the Prevention and Reactivation Centre (PRC); (3) Availability of multidisciplinary geriatric expertise; (4) Provision of support and consultation of relevant professionals to informal caregivers; (5) Intensive follow-up throughout the entire chain of care by a casemanager with geriatric expertise. Outcome and process evaluations are ongoing and results will be published in a series of future papers. Trial registration The Netherlands National Trial Register: NTR2317